Could Cells from Your Nose Fix Your Heart? Transplantation of Olfactory Stem Cells in a Rat Model of Cardiac Infarction. (2010) - McDonald, Cameron; Mackay-Sim, Alan; Crane, Denis; Murrell, Wayne
Abstract : This study examines the hypothesis that multipotent olfactory mucosal stem cells could provide a basis for the development of autologous cell transplant therapy for the treatment of heart attack. In humans, these cells are easily obtained by simple biopsy. Neural stem cells from the olfactory mucosa are multipotent, with the capacity to differentiate into developmental fates other than neurons and glia, with evidence of cardiomyocyte differentiation in vitro and after transplantation into the chick embryo. Olfactory stem cells were grown from rat olfactory mucosa. These cells are propagated as neurosphere cultures, similar to other neural stem cells. Olfactory neurospheres were grown in vitro, dissociated into single cell suspensions, and transplanted into the infarcted hearts of congeneic rats. Transplanted cells were genetically engineered to express green fluorescent protein (GFP) in order to allow them to be identified after transplantation. Functional assessment was attempted using echocardiography in three groups of rats: control, unoperated; infarct only; infarcted and transplanted. Transplantation of neurosphere-derived cells from adult rat olfactory mucosa appeared to restore heart rate with other trends towards improvement in other measures of ventricular function indicated. Importantly, donor-derived cells engrafted in the transplanted cardiac ventricle and expressed cardiac contractile proteins.